Long‐Term Effects of Peatland Cultivation on Soil Physical and Hydraulic Properties: Case Study in Canada. Issue 6 (20th March 2015) - Hallema, Dennis W.; Lafond, Jonathan A.; Périard, Yann; Gumiere, Silvio J.; Sun, Ge; Caron, Jean
Abstract : Organic soils are an excellent substrate for commercial lettuce ( Lactuca sativa L.) farming; however, drainage accelerates oxidation of the surface layer and reduces the water holding capacity, which is often lethal for crops that are sensitive to water stress. In this case study, we analyzed 942 peat samples from a large cultivated peatland complex (18.7 km 2 ) in southern Quebec, Canada, and demonstrated from spatial and temporal patterns that agriculture resulted in a compacted layer below the root zone. We grouped the samples based on the year in which the corresponding fields were created on the previously undisturbed peatland (cutoff years 1970, 1980, 1990, and 2000) and discovered that bulk density has continued to increase, partly due to the overburden pressure, while organic matter has continued to decline since the fields were reclaimed and drained in phases between 1955 and 2006. Saturated hydraulic conductivity ( K s ) in the upper 20 cm was remarkably lower on fields older than 10 yr ( p = 0.0973 for Wilcoxon rank test), with more samples having a K s < 2.0 × 10 −3 yr. Soil water available capacity (SWAC) was between approximately 5 and 33 cm on fields reclaimed after 2000, while samples from fields reclaimed before 2000 had a lower SWAC between 2 and 23 cm (groups discernable at p = 0.0203). It is possible, however, that the greatest rate of change in K s and SWAC occurred within even a year of reclamation. The results of this study call for active measures to reduce organic soil degradation such as reducing tillage and on‐field traffic or following a crop rotation scheme.